Regulation of T cells by mTOR: the known knowns and the known unknowns. Issue 1 (January 2015) - Pollizzi, Kristen N.; Powell, Jonathan D.
Highlights mTOR has emerged as a critical integrator of cues from the immune microenvironment. By coordinating immunologic and metabolic programs, mTOR guides T cell fate decisions. Mechanisms by which mTOR activity impacts T cell differentiation are not fully defined. Contradictory findings highlight areas requiring further investigation.